A versatile geometric metasurface for generating both focused vortex and vector beams - Qiao Jiang; Xiangdong Guo; Hong Xiang; Dezhuan Han (Results in Physics, 2023)
Singular beam has attracted lots of research interests because of its great potential for applications in various fields such as optical communications and super-resolution imaging. To meet the increasing demands of integrated photonic systems, miniaturized devices for generating singular beams are required. Here, a coherent approach is proposed to design metasurfaces for polarization-controllable generation of focused singular beams with phase or polarization singularity. Metasurfaces with different topological charges configuration are designed, and the capability of generating focused optical vortices with arbitrary topological charges pair and required focusing performance is demonstrated. Furthermore, it is demonstrated that both focused vortices and cylindrical vector beams can be generated and controlled easily by incident polarization. The flexibility and versatility of the proposed approach may provide new opportunities to realize compact and multifunctional singular optical devices for applications including optical tweezers, light-matter interaction, optical communication, and other related fields.